KC and the Sunshine Band present Get down tonight. the disco explosion : live - Lubinsky, T. J. (My music (series from PBS), 2004)
The smash PBS concert special "KC And The Sunshine Band Present Get Down Tonight : The Disco Explosion," taped on August 17, 2004, at the Convention Hall in Asbury Park, New Jersey, celebrates the disco era with original artists singing their biggest hits in front of an enthusiastic audience.